Design and prototyping of a test facility to investigate the transport properties of dilute phase gas-particle flows applicable to coal-fired power plants - Du Sart, Colin F (Department of Mechanical Engineering, 2017)
Understanding the properties of dilute phase gas-particle transport and the applicability of the different empirical correlations found in literature for these properties are crucial in the study of Pulverized Fuel conveying applicable to South African coal-fired power plants. Having access to a test facility in which empirical data can be generated under controlled operating conditions would enhance this understanding and will allow more informed application of these correlations. The aim of this thesis was to develop a concept design and prototype of a pneumatic conveying test facility that can be used to evaluate these empirical correlations and property relationships. A comprehensive literature review was conducted of the empirical correlations available and a study was conducted to determine the scaling required to achieve similarity. A theoretical process model was also developed together with a methodology to determine the operating envelope of the blower. The model and methodology were subsequently used in the design of a prototype test facility that would demonstrate the critical particle feed and extraction processes, and to derive suitable specifications for the blower. The prototype, including a complete data acquisition and control system, was developed, constructed and commissioned in cooperation with a commercial engineering company. The facility allows for the control, online measurement and recording of the gas and particle mass flow rates. Practical tests were then conducted with Fly Ash, as a substitute for Pulverized Coal, to demonstrate the particle feed and extraction processes and to evaluate the accuracy of control of the gas and particle mass flow rates. Tests were conducted for loadings (particle to gas mass flow ratios) between 0.988 and 6.860 at gas mass flow rates between 0.051 and 0.115kg/s and particle mass flow rates between 0.077 and 0.600kg/s. A methodology to determine the particle mass flow rate and its associated uncertainty from the Loss In Weight and Gain In Weight systems was developed from basic principles and demonstrated. The relative uncertainties calculated for the measured particle mass flow rates are less than ±1% for all tests. The maximum relative uncertainties calculated for the measured gas mass flow rates and loadings are ±6%. The conceptual overall system layout for the final test facility, including the instrumentation design, was then refined based on the experience gained and recommendations are made for consideration in the detail design. The conceptual design allows for the control of the gas and particle mass flow rates as well as the gas temperature and pressure level. The final test facility will be suitable to conduct pressure drop tests, saltation and choking tests, as well as mass balances and visual observations. The process model and methodologies developed here may now be applied in the detail design and operation of such a final test facility.